Estratégias de construção de faces no ciberespaço: assédio sexual em cena - Ribeiro, Vivian Araújo Fontes (2018)
In Politeness Theory studies, all face-to-face verbal interaction is intrinsically threatening, as speakers, by coming into contact with one another, promote imbalance of faces and use strategies to protect them. Generally, politeness is seen as a linguist ic behavior used by the speaker to minimize the risks of communication and make it more harmonious. In this way, the interlocutors adopt strategies of face preservation, since the concern with the social image is clearly observed in the individuals. This study aims to reflect on face preservation strategies, prosecution and linguistic politeness in two letters addressed to the public and online commentaries on the case in which the actor Jose Mayer Drumond, 67, and the costume designer Susllem Meneguzzi Tonani, 28, were involved. This sample was collected in two journalistic articles published on the G1 and Folha de São Paulo news sites on March 31st and April 4th, 2017, and the online comments chosen were among 381 comments made on one of the articles. Then, we analyze the linguistic behavior and the way in which face-building strategies materialize in the interactions, with the objective of investigating the accusations of macho motivation as face preservation. This analysis is based on the following questions: i) Do the journalistic articles about this fact convey polished effects? ii) Did the speeches of the journalists, José Mayer and the people who commented also carry polished effects? iii) How are these effects structured? iv) How did the actor José Mayer use the politeness strategies to make his clarification note and maintain the image of himself in the face of a controversy? v) To what extent do the readers of the articles that have commented on the internet harmoniously reconcile self-preservation and respect for the other? In order to account for such a proposal, the theoretical contribution of Brown and Levisnson's model of politeness (2011 [1987]) and the reformulations made by Kerbrat- Orecchioni (2006) are used. It also gives rise to works such as Armengaud (2006), Pinto (2001), Paveau and Sarfati (2006), which deal with major theories of Linguistics and, specifically, with Pragmatics. In general, the results obtained in the analysis point to a greater use of strategies of politeness by the actor, since it needs to maintain a balance in the personal relationships established with the public. The costume designer shows that she wants to deconstruct his face, without the need to preserve hers. Likewise, some online commentary shows outrage at the whistleblower for not having denounced the actor before or for having interrupted the complaint he had made, since commentators have no need to soften the threat to her face.